Trust in Religious Stewardship and Waqf Intention in Islamic Tourism Governance: Exploring Community Participation, Transparency, and Circular Economy through the SOR Model - Yulfan Arif Nurohman; Jati Waskito; I Imronudin (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study investigates the role of trust, transparency, and community participation in shaping waqf intentions within the context of Islamic religious tourism in Indonesia. Referring to the Stimulus-Organism-Response (SOR) framework integrated with the principles of Community-Based Tourism (CBT), this research examines how external stimuli, community participation, circularity visibility, and transparency influence the internal psychological mechanism of trust in religious management and subsequently affect behavioral responses in the form of waqf intentions. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed using data from 210 respondents at mosque-based religious tourism destinations in Central Java. The findings reveal that community participation and transparency significantly enhance trust, whereas circularity has no significant effect. Furthermore, trust is positively associated with the waqf intentions of religious tourism visitors. The results highlight that moral legitimacy and spiritual integrity outweigh environmental circularity in building public trust in Islamic philanthropic institutions. This study contributes to theory by extending the application of SOR to Islamic philanthropy and to practice by offering a sustainable governance model for mosque-based tourism through transparent, participatory, and trust-oriented management.